The Role of Biophysical Stickiness on Oil-Mineral Flocculation and Settling in Seawater - Ye, Leiping; Manning, Andrew J.; Holyoke, James; Penaloza-Giraldo, Jorge A.; Hsu, Tian-Jian (Frontiers in Marine Science, 2021)
Bio-physical cohesive particles in aquatic systems, such as Extracellular polymeric substances (EPS) and mineral clay, play an important role in determining the transport of spilled oil contamination and its eventual fate given that suspended sediment and microbial activities are often prevalent and diverse in natural environments. A series of stirring jar tests have been conducted to understand the multiple structures characteristics of the oil-mineral aggregates (OMAs) and EPS-oil-mineral aggregates (EPS-OMAs) with two types of common mineral (Kaolinite and Bentonite) aggregates. OMAs and EPS-OMAs have been successfully generated in the laboratory with artificial seawater, Texas crude oil (Dynamic viscosity: 7.27×10-3 Pa·s at 20 ℃), natural clay minerals (Bentonite and Kaolin clay), and Xanthan gum powder (a proxy of natural EPS) using a magnetic stirrer providing a homogenous turbulent flow with a high turbulence level similar to that under breaking waves. The high-resolution microscopy results show that EPS, kaolinite, and bentonite lead to distinguished oil floc structures because of the different stickiness character of EPS and mineral clay particles. With relatively low cohesion, kaolinite particles tend to attach to oil droplets surface and become dominant in small-sized flocs in the mixture sample. Bentonite particles with higher cohesion can absorb with oil droplets and are dominant in large-sized flocs. Biological EPS with the highest cohesion can bond multiple small oil droplets and form a web structure trapping oil and minerals. In the EPS, minerals, and oil mixture, oil prefers to aggregate with bentonite than kaolinite, and EPS contributes to forming more extra-large size flocs ( 900 microns) with low density ( 0.02 mm·s-1). The settling velocity of the OMAs and EPS-OMAs are highly related the mineral types and EPS components.